A Novel Method to Recognise Faults and Reefs from History Matching of Gas Production- Case Study: Mishrif Reservoir, Southern Iraq - Al-Rikaby, Alaa Shihan; Al-Jawad, Mohammed Saleh (Iraqi Journal of Science, 2025)
The study area is located within the Mesopotamian Basin, the habitat of several oil fields that extract hydrocarbons from NW-SE-trending anticline formations parallel to the Zagros folding belt. The study aimed to determine if discrepancies in bubble pressure values were caused by faults or reefs using historical matching of gas production. The study revealed a distinct Mishrif reservoir seismic graph and seismic reflectors exhibiting many severe discontinuities, indicating the presence of a reef or fault. Field production data matched the fault case more consistently than the reef case during reservoir simulation, as per the well results (C37P, C43P, C46P). The history-matching simulation confirmed the two faults and rejected the reef. After seismic interpretation and historical matching, the Mishrif reservoir has two faults that were the cause of the bubble point pressure discrepancy during production operations. This method is suitable for discovering geological structures and deformations that cause bubble pressure differences for use by other researchers.